Temporal and spatial evolution of NDVI in seasonal freezethawing area of China (Bangladesh Journal of Botany, 2021)
Vegetation is the most important composition part of land ecological system and is sensitive to the change of global climate. The characteristic of nearly 37a temporal and spatial evolution of NDVI in China’s seasonal freezing-thawing area was studied focusing on the target of China’s seasonal freeze-thawing area, utilizing methods of GIS spatial analysis and mathematical statistics and based on the dataset of AVHRR GIMMS NDVI and MODIS NDVI during 1982 to 2018. It showed that nearly 37a NDVI in China’s seasonal freezing-thawing area fluctuated with an increasing trend in the range of 5.292~6.635. Besides, the coverage degree of vegetation increased dramatically. Sandy land developed from the direction of desertification to oasisization. This work provides scientific evidence for the sandy land ecological evaluation of China’s seasonal freezing-thawing area and regional sustainable development.Bangladesh J. Bot. 50(3): 847-853, 2021 (September) Special